PERBANDINGAN HASIL UJI KAPASITAS DUKUNG TIANG PANCANG PADA TANAH LEMPUNG JENUH SKALA LABORATORIUM DENGAN PERHITUNGAN ANALISIS STATIS - Gumbert Maylda Pratama (Jurnal Teknik Sipil, 2021)
Pile bearing capacity, is an important parameter in infrastructure design. The pile driving process, especially in saturated clay soils, results in an increase in pore pressure which affects the bearing strength capacity of the pile foundation immediately after erection. By knowing the com-parison of various ways to calculate the bearing capacity of a pile foundation, especially in clay soils, various influencing parameters can be studied and to be taken in determining the bearing ca-pacity of a pile foundation. The test is carried out by comparing the value of the pile bearing capacity of a laboratory scale pile model with the results of the calculation of the pile bearing capacity using the static analysis method based on the results of the test parameters of the soil. The clay soil con-ditions in the test are limited to saturated conditions. The reading of the change in pore water pres-sure is carried out using a pressure transducer during the pile driving process. Based on the pile loading test results in the laboratory, the pile bearing capacity results were 0.31 kN, while the bearing capacity results based on the static analysis method were 0.75 kN. The difference in pile bearing carrying capacity is caused by excess pore water pressure that appears around the ground during the driving process.